Dysregulated eating behaviour, eating disorders and obesity - Schmidt, Ulrike (Henry Stewart Talks, 2015)
Terminology, classification & epidemiology, Binge eating disorder (BED) vs. Bulimia nervosa (BN), Clinical features of bulimic disorders, Aetiology of bulimic behaviours/disorders, Various treatments, outcomes and future directions